تحریکِ استشراق کےاسباب ومقاصد؛ایک تجزیاتی مطالعہ : An analytical study of the Aims and Motivations of the Orientalism Movement - Ali Awais, Mian Muhammad; Ahmad, Prof. Dr. Matloob (Al-Amīr Research Journal for Islamic Studies, 2024)
The Orientalism movement, driven by Western fascination, aimed to reject and convert Muslims to Christianity through the construction of hegemonic narratives and stereotypes. Motivated by religious superiority and colonial expansion, Orientalism perpetuated power imbalances while shaping global perceptions and identities. Understanding its aims unveils its role in the complex interplay of cultural, political, and religious dynamics. This study delves into how these narratives influenced policies and literature of the time, highlighting the lasting impact of Orientalist discourse on modern-day perspectives and the ongoing challenges it presents in fostering cultural understanding and equality. Keywords: Muslim, Orientalism, Aims, Motivations, Identities